Sunflower Marketing in the High Plains - O’Brien, Daniel; Stockton, Roger; Belshe, Dana J. (My University, 2001)
This publication addresses basic issues related to sunflower marketing in the High Plains, including Kansas, Colorado, and Nebraska.
L887_2001-09
Keywords: L887; Crops; L